Penerapan Wacana Dalam Konteks Perdagangan Di Pasar Bei Abuk Betun - Yustina Sako; Joel Tasmam (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
One form of communication is discourse. Discourse means 'performing speech acts', discourse can be in oral or written form. Discourse is an attempt to understand linguistic elements because the distinguishing element between discourse and non-discourse lies in the presence or absence of a unified meaning. One form is conversational description and exposition, where this discourse aims to describe a real situation and convey facts in an orderly, logical, interconnected manner with the aim of explaining ideas, terms, problems, processes, etc. so that they are known. by other people. This discourse is appropriate to use for interactions in the field of commerce, because it tries to explain and invite someone to be interested in what we describe and explain.